The XylS/Pm regulator/promoter system and its use in fundamental studies of bacterial gene expression, recombinant protein production and metabolic engineering. Issue 4 (9th March 2017) - Gawin, Agnieszka; Valla, Svein; Brautaset, Trygve
Summary: The XylS/ Pm regulator/promoter system originating from the Pseudomonas putida TOL plasmid pWW0 is widely used for regulated low‐ and high‐level recombinant expression of genes and gene clusters in Escherichia coli and other bacteria. Induction of this system can be graded by using different cheap benzoic acid derivatives, which enter cells by passive diffusion, operate in a dose‐dependent manner and are typically not metabolized by the host cells. Combinatorial mutagenesis and selection using the bla gene encoding β‐lactamase as a reporter have demonstrated that the Pm promoter, the DNA sequence corresponding to the 5′ untranslated end of its cognate mRNA and the xylS coding region can be modified and improved relative to various types of applications. By combining such mutant genetic elements, altered and extended expression profiles were achieved. Due to their unique properties, obtained systems serve as a genetic toolbox valuable for heterologous protein production and metabolic engineering, as well as for basic studies aiming at understanding fundamental parameters affecting bacterial gene expression. The approaches used to modify XylS/ Pm should be adaptable for similar improvements also of other microbial expression systems. In this review, we summarize constructions, characteristics, refinements and applications of expression tools using the XylS/ Pm system. Abstract : This review summarizes history of application of the novel XylS/ Pm regulator/promoter system as a flexible expression cassettte system with a wide range of applications in microbial molecular biology. It describes its wide application range and how this system has been modified and used to unravel new basic insight into bacterial gene expression.